(untitled) (Global Journal of Human-Social Science, 2023)
The use of new technologies in the process of educational intervention is undoubtedly a basic and valuable tool for teachers Specifically using new forms of representation of educational content and providing a teaching practice that enhances the user s visual perception of the real environment is a key factor favoring the educational inclusion of students with special educational needs In the present study we will investigate whether teachers believe that the use of augmented reality AR in children with autism affects their social skills as well as the possibilities of augmented reality in enhancing the communication skills of children with ASD in areas speech social interaction pretend play reading enhancing visual perception imitative ability attention management and perception of the physical world